Cystic Fibrosis Database (CFDB): A new web‐based tool for cystic fibrosis specialists. Issue 9 (16th February 2014) - Buzzetti, Roberto; Cirilli, Natalia; Minicucci, Laura; Raia, Valeria; Salvatore, Donatello; Maffeis, Paolo
Summary In order to help specialists involved in CF care and clinical research to know the current best evidence about clinical effectiveness of interventions in CF, we designed and developed a web‐based, free access tool called "CFDB"—Cystic Fibrosis DataBase (www.inetflow.it/CFDB). The database was built by searching in Medline, Embase, Cochrane Library and worldwide trials registries all studies involving clinical interventions in CF. The tool lets the user define queries starting from one or more types of pathological conditions and one or more interventions. The output of the queries is structured in three levels: (1) how many and which studies deal with the conditions formulated in the query; (2) which are the main results of these studies; (3) a critical summary of the literature related to the query. This tool, providing a quick overview of the available evidence in clinical research in CF, may help clinical decision making, designing of new trials and building guidelines. Pediatr Pulmonol. 2014; 49:938–940. © 2014 Wiley Periodicals, Inc.